Students’ Autonomous Learning in Online Class - Elfila Luhdyanti; Vitri Angraini Hardi (Universitas Pahlawan Tuanku Tambusai, 2020)
This research aims to describe the students' autonomous learning in online class and find out the problems in online class at University of Pahlawan Tuanku Tambusai. This is a descriptive research. The participants are the second, fourth, and sixth semester students of English Language Education Study Program. The researchers used questionnaire as the instrument. There were two results gained from the study. First, based on the discussion on the implementation of autonomous learning, autonomous learning was implemented by integrating metacognitive strategies that use learning process, planning for learning, monitoring the learning task, and evaluating. Second, based on the discussion, the students' perception of autonomous learning in online class, most of the students had positive perception of autonomous learning. The students become more active learn in online class. The students could design the learning material independently. However, there are some difficulties in implementing online learning activities, students have limitations in understanding the material they learned. With respect to research findings, it has to be designed based on the learning process as usual. It is just that in this case students were not familiar with the independent learning process in online classrooms